Contactless radio frequency probes for high‐temperature characterisation of microwave integrated circuits. Issue 11 (1st May 2014) - Jordan, J.L.; Simons, R.N.; Zorman, C.A.
Abstract : The first ever demonstration of a viable contactless radio frequency (RF) probing technique at elevated temperatures is presented. The design utilises an inverted microstrip design for the probe, which is suspended over and placed in close proximity to the input/output microstrip lines of the device under test to couple signals in and out. To demonstrate the efficacy of the contactless RF probing technique, three example circuits, namely, a microstrip spurline bandstop filter, a microstrip pin diode series switch and a monolithic microwave integrated circuit amplifier mounted on a microstrip line were designed, fabricated and performance measured against temperature up to 200°C.